Bilateral Ovariectomy Decreases the Levels of Cyclic Nucleotides and Nuclear Phosphorylated Estrogen Receptor-Alpha in Memory-Sensitive Rat Brain Regions - Goyal, Ahsas; Garabadu, Debapriya (Indian Journal of Pharmaceutical Education and Research, 2020)
Aim/Background: The level of phosphorylated Estrogen Receptor alpha (ERα) in the nucleus was investigated in different memory-sensitive brain regions of estrogendeficient female rats. Further, the levels of cyclic nucleotides were estimated in those brain regions to draw a possible correlation with phosphorylated ERα signaling. Materials and Methods: Bilateral ovariectomy was performed on the first day of the experimental schedule of 60 days. Behavioural analysis was performed and various biochemical parameters were assessed in discrete brain regions of rat. Results: Ovariectomy caused a significant deterioration in learning and memory of the animals in terms of increase in transfer latency, decrease in time spent and percentage of total distance traveled in the target quadrant in Morris Water Maze (MWM) test protocol. Further, ovariectomy reduced the spontaneous alteration behavior of the rats in the Y-maze test. There was a significant increase in cholinergic dysfunction in respect of decrease in the activity of choline acetyltransferase and level of acetylcholine and an increase in the activity of acetylcholinesterase in rat hippocampus, pre-frontal cortex and amygdala. Subsequently, ovariectomy significantly reduced the extent of phosphorylation and translocation of ERα in such rat brain regions. Moreover, ovariectomy caused a decrease in the levels of cyclic nucleotides such as cAMP and cGMP in these rat brain regions. Additionally, there was a significant positive correlation between the ratio of cyclic nucleotides (cGMP/cAMP) and nuclear p-ERα in all brain regions of these ovariectomized animals. Conclusion: The cyclic nucleotides could be a potential and alternate target to promote the phosphorylated ERα receptor-mediated mechanism during memory formation in estrogen deficiency condition.
Keywords: Bilateral ovariectomy; Estrogen receptor alpha (ERα); Cyclic nucleotides; Ligand-independent mechanism; Cholinergic activity; Memory